2022
DOI: 10.1371/journal.pone.0273379
|View full text |Cite
|
Sign up to set email alerts
|

Driving the pulse of the economy or the dilution effect: Inflation impacting economic growth

Abstract: Economic growth becomes a critical component in the development of every country since it enhances living standards and other related concerns while eliminating poverty. As a developing country, Sri Lanka must place more emphasis to achieve sustainable economic growth. In addition, various factors have positive and negative impacts on economy’s growth. As such, the specific goals of any economy are to sustain long-term economic growth and low inflation. As a result, generally, high inflation is destructive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…The results of this research are consistent with the study conducted by Atigala (2022), which concluded that inflation has negative and significant effect on economic growth in the short term. Futhermore, Quddus (2022) study concluded that inflation in tha short term and long term has a negative and significant effet on economic growth.…”
Section: The Effect Of the Inflation On Economic Growth In Indonesiasupporting
confidence: 91%
“…The results of this research are consistent with the study conducted by Atigala (2022), which concluded that inflation has negative and significant effect on economic growth in the short term. Futhermore, Quddus (2022) study concluded that inflation in tha short term and long term has a negative and significant effet on economic growth.…”
Section: The Effect Of the Inflation On Economic Growth In Indonesiasupporting
confidence: 91%
“…The same econometric instrument did not reveal a statistically significant relationship between the variables in the short run but confirmed this relationship in the long run. In turn, the case of Sri Lanka confirmed the negative impact of the inflation increase both in short-and long-run perspectives: a 1% increase in inflation stagnated economic growth by 3,427.94 mln USD in the short run and 107,263.8 mln USD in the long run (Atigala et al, 2022). These controversial modeling results might be explained not only by temporal patterns but also by geographical patterns and specific features of macroeconomic situation.…”
Section: Literature Reviewmentioning
confidence: 88%
“…FDI and economic growth relationship cannot be generalized mainly because it is highly subject to alteration with changing institutional, policy, and regulatory environment (Herzer et al 2008). The relationship between inflation and economic growth in developing countries is a subject on which there are still very wide differences of opinions (Wai 1959) The economists believe that appropriate rate of inflation is essential for economic growth, whereas the monetarists see inflation is detrimental to economic progress (Salian, n.d.) (Atigala et al 2022).…”
Section: A Theoretical Evidencementioning
confidence: 99%